2008
DOI: 10.1177/1078087408314774
|View full text |Cite
|
Sign up to set email alerts
|

Social Disorganization, Drug Market Activity, and Neighborhood Violent Crime

Abstract: Although illicit drug activity occurs within local communities, past quantitative research on drug markets and violent crime in the United States has been conducted mainly at the city level. The authors use neighborhood-level data from the city of Miami to test hypotheses regarding the effect of drug activity and traditional indicators of social disorganization on rates of aggravated assault and robbery. The results show that drug activity has robust effects on violent crime that are independent of other disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 30 publications
5
85
0
Order By: Relevance
“…Furthermore, findings showed that residential mobility is the most important predictor of crimes against property, and disorganization in the neighborhood is strongly related to conduct problems in children (Lambert, Brown, Phillips, & Ialongo, 2004). Little and Steinberg (2006) and Martinez, Rosenfeld, and Mares (2008) found that drug trafficking was influenced by neighborhood-disadvantage indicators. Juveniles living in disadvantaged neighborhoods were more at risk of engaging in these kinds of activities.…”
Section: Neighborhood Variables In Adolescent Offendingmentioning
confidence: 95%
“…Furthermore, findings showed that residential mobility is the most important predictor of crimes against property, and disorganization in the neighborhood is strongly related to conduct problems in children (Lambert, Brown, Phillips, & Ialongo, 2004). Little and Steinberg (2006) and Martinez, Rosenfeld, and Mares (2008) found that drug trafficking was influenced by neighborhood-disadvantage indicators. Juveniles living in disadvantaged neighborhoods were more at risk of engaging in these kinds of activities.…”
Section: Neighborhood Variables In Adolescent Offendingmentioning
confidence: 95%
“…1 In contrast to person-specific drug markets that are largely sustained through social networks, hidden, and may not be geographically bounded, 5 visible drug markets are characterized by place, facilitating accessibility, drug tourism (e.g., traffic of non-residents to a given neighborhood to purchase drugs), and profit. [5][6][7] Visible drug market activity bears negative implications upon residents living in proximity by glorifying risk behaviors to youth, stigmatizing and marginalizing communities, 5 and serving as a potential determinant of violence, 8 sexually transmitted diseases, 9 and drug abuse. 10,11 Baltimore City is among several US cities where visible drug market activity occurs in some communities and has been associated with economic deprivation, poor housing stock, and social disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Drug-related crime has also been linked to neighborhood characteristics [22][23][24]. Drug-related crime is a major problem in our society; it has negative repercussions on health, creates personal and social conflicts, and can perpetuate community deterioration [24,25].…”
Section: Introductionmentioning
confidence: 99%